2019
DOI: 10.16899/jcm.684344
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Neuroimaging of Patients with Vertigo in Emergency Department

Abstract: Introduction: The fact that many diseases cause symptoms of vertigo and that some of them are life-threatening make it difficult to manage vertigo in emergency departments (ED). Parallel to these difficulties, the number of neuroimaging use in diagnosis is increasing. In this study, it is aimed to evaluate the neuroimaging costs of patients with vertigo in ED. Methods: The study was carried out with a retrospective review of the files of the patients with vertigo who were admitted to ED between 01.01.2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…21 Additionally, our study's proportion of patients undergoing neuroimaging (70.98%) surpasses figures from related research conducted in a Turkish emergency department (28%). 22 A systematic review which included studies from developed countries identified three main drivers of increased direct costs including excessive use of diagnostic imaging and excessive use of emergency care.15 In addition, the duration of hospitalization is also associated with an increase in cost, that is increase in the length of stay results in higher costs. 23 This financial burden can have a direct impact on the patients and their families especially in low and low-middle-income countries where out-of-pocket payment is the primary of medical-bill payments instead of third-party or medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…21 Additionally, our study's proportion of patients undergoing neuroimaging (70.98%) surpasses figures from related research conducted in a Turkish emergency department (28%). 22 A systematic review which included studies from developed countries identified three main drivers of increased direct costs including excessive use of diagnostic imaging and excessive use of emergency care.15 In addition, the duration of hospitalization is also associated with an increase in cost, that is increase in the length of stay results in higher costs. 23 This financial burden can have a direct impact on the patients and their families especially in low and low-middle-income countries where out-of-pocket payment is the primary of medical-bill payments instead of third-party or medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most common clinical symptoms and reasons for admission to the emergency department and outpatient clinics. [1,2] It affects approximately 20-30% of the world population and also decreases the quality of life of patients. [3] Peripheral vertigo (PV) is a type of vertigo that usually occurs due to infections of the inner ear such as otitis and labyrinthitis.…”
Section: Introductionmentioning
confidence: 99%